2009
DOI: 10.4269/ajtmh.2009.80.678
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk of Hantavirus Infection in Beijing, People’s Republic of China

Abstract: To understand the spatial distribution of hantavirus infections across landscapes and its influencing environment factors in Beijing, People's Republic of China, rodents captured in this region were examined for hantavirus by reverse transcription-polymerase chain reaction. A total of 1,639 rodents were trapped at 86 randomly selected sites. The overall infection rate for hantavirus was 7.14% in the rodents. Multivariate logistic regression analysis indicated that the natural infection rates for hantavirus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…6,7,11,12 Some studies found that temperature had a positive effect, 6,11 and others found a negative effect on HFRS incidence. 7,12,13 The present study showed that monthly maximum temperature was positively associated with the monthly number of HFRS cases in this province, and other temperature factors, such as monthly minimum temperature and monthly mean temperature, were not included in the final model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6,7,11,12 Some studies found that temperature had a positive effect, 6,11 and others found a negative effect on HFRS incidence. 7,12,13 The present study showed that monthly maximum temperature was positively associated with the monthly number of HFRS cases in this province, and other temperature factors, such as monthly minimum temperature and monthly mean temperature, were not included in the final model.…”
Section: Discussionmentioning
confidence: 99%
“…14 Studies in different areas have suggested that climate factors, such as temperature, precipitation, and relative humidity, may influence the incidence of HFRS. [6][7][8] However, the role of climate factors in the transmission of HFRS differs in different regions. 4,[6][7][8][9][10][11][12] For example, increased grass seed production followed by heavy precipitation, as a result of the El Niñ o Southern Oscillation (ENSO), was found to be associated with higher Peromyscus maniculatus rodent density in southwestern United States and provides reservoirs for Sin Nombre virus.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations